(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
Black seed (Nigella sativa) is a widely used medicinal plant throughout the world. Seeds and oil have a long history of folklore usage in various systems of medicines and food. The fruits of jujube (Ziziphus jujuba) are being consumed all around the world because of their health benefits, as both food and herbal medicine. The aim of this research was to evaluate Proximate and elemental compositions of Black seed and Jujube as formulation for managing peptic ulcer. Proximate composition of jujube, black seed and formulation of black seed and jujube was carried out and the contents of moisture, carbohydrate, fats, fibers, proteins and ash were determined according to standard AOAC, 2010 method. Mineral elements (Zn, Fe, Cu, Cr, Mg, Ca, Na, K, As, Pb) were also determined by atomic absorption spectrophotometric method. The result revealed that jujube has higher carbohydrate, fiber and ash contents of 46.60%, 32.17% and 12.87% respectively, while black seed has higher fats and crude protein contents (35.9% and 9.47% respectively). Elemental composition revealed that black seed has higher zinc, iron, copper, and sodium contents of 1.91 mg/L, 6.95 mg/L, 2.42 mg/L, and 27.23 mg/L respectively. Black seed and jujube can be consumed alone or in combination as they are highly enriched with nutrients which are essential for physiological body functioning and can facilitate healing in ulcer treatment.